Modification of the Model of Strategic Development of Companies with Regard to Exogenous Factors (Economic journal of Lesya Ukrainka Volyn National University, 2016)
A critical analysis of existing models of strategic development of the company was conducted and concluded had been made that the necessity exists for further development towards appropriate combination of models based on the life cycle concept and models based on external factors influence. Hypothesis was formulated regarding the impact of socio-psychological factors and values on the strategic development of the organization. The ways of empirical test of this hypothesis are proposed
Keywords: Strategic development of the company, organization life cycle, values, socio-psychosocial factors, cultural dimensions